1994
DOI: 10.1113/expphysiol.1994.sp003783
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oesophageal distension on diaphragm and laryngeal muscle activity in the anaesthetized cat

Abstract: SUMMARYThe electromyographic (EMG) activities of diaphragm and laryngeal muscles were recorded during oesophageal distension in anaesthetized cats. The responses to distension of the thoracic oesophagus differed from those evoked by distension of the cervical oesophagus. The crural component of the diaphragm (CD) was inhibited by distension of the thoracic oesophagus; distension of the cervical oesophagus did not affect CD EMG. Thyroarytenoid (TA) muscle EMG increased markedly and consistently in response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Dramatic divergence of the activity of the crural and costal diaphragm is seen during swallowing and oesophageal distension. This selective crural inhibition evoked by balloon distension of the oesophagus has been reported by many researchers (Cherniack et al 1984;Altschuler et al 1985;Oliven et al 1989;Oyer et al 1989a;Holland et al 1994;Jones et al 1994;Liu et al 2000).…”
Section: Oesophageal Distension and Crural Diaphragm Relaxationsupporting
confidence: 77%
See 1 more Smart Citation
“…Dramatic divergence of the activity of the crural and costal diaphragm is seen during swallowing and oesophageal distension. This selective crural inhibition evoked by balloon distension of the oesophagus has been reported by many researchers (Cherniack et al 1984;Altschuler et al 1985;Oliven et al 1989;Oyer et al 1989a;Holland et al 1994;Jones et al 1994;Liu et al 2000).…”
Section: Oesophageal Distension and Crural Diaphragm Relaxationsupporting
confidence: 77%
“…The precise mechanism that mediates the reflex inhibition of the crural diaphragm during oesophageal distension is still somewhat unclear. In certain studies, bilateral vagotomy was seen to abolish the reflex Cherniack et al 1984;Oyer et al 1989a;Jones et al 1994). Although it has been suggested that vagal afferents from the oesophagus exert an inhibitory influence on the brainstem inspiratory neurones controlling the crural diaphragm, Altschuler et al (1987) could not demonstrate any inhibition of medullary inspiratory neurones in response to oesophageal distension in the cat.…”
Section: Oesophageal Distension and Crural Diaphragm Relaxationmentioning
confidence: 98%